1993
DOI: 10.1071/ch9930977
|View full text |Cite
|
Sign up to set email alerts
|

The Alkaloids of Ophiorrhiza filistipula

Abstract: Extraction of the fresh leaves of Ophiorrhiza filistipula ( Rubiaceae ) has yielded the alkaloids normalindine (2), 7-methoxycamptothecin (6) and strictosidinic acid (II). The configurations of the Strychnos alkaloids dolichantoside and isodolichantoside are revised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 0 publications
2
30
0
1
Order By: Relevance
“…Several Ophiorrhiza species (of the family Rubiaceae) such as O. mungos, O. filistipula, O. pumila, O. liukiuensis, O. prostrata have been reported as the new sources of CPT production (Tafur et al 1976, Arbain et al 1993, Saito et al 2001, Sudo et al 2002, Kitajima et al 2005, Beegum et al 2006, respectively. As O. japonica, one indigenous Chinese medicinal plant commonly used for ulcers, poisonous wounds and leprosy in China, belongs to Ophiorrhiza genus, it is speculated that CPT analogues may also exist in its roots.…”
mentioning
confidence: 98%
“…Several Ophiorrhiza species (of the family Rubiaceae) such as O. mungos, O. filistipula, O. pumila, O. liukiuensis, O. prostrata have been reported as the new sources of CPT production (Tafur et al 1976, Arbain et al 1993, Saito et al 2001, Sudo et al 2002, Kitajima et al 2005, Beegum et al 2006, respectively. As O. japonica, one indigenous Chinese medicinal plant commonly used for ulcers, poisonous wounds and leprosy in China, belongs to Ophiorrhiza genus, it is speculated that CPT analogues may also exist in its roots.…”
mentioning
confidence: 98%
“…On the basis of spectroscopic analysis, it was proposed to be an unusual N b -C20 secooxindole gelsedine-type alkaloid (15). However, during the reinvestigation of the chemical constituents of G. elegans, we found that gelsemoxonine (16) had an unusual azetidine unit (Fig. 5) [9].…”
Section: Alkaloids In Gelsemium Elegansmentioning
confidence: 97%
“…6) [9,10]. 14,15-Dihydroxygelsenicine (18) [9] was presumed to be the biosynthetic precursor of gelsemoxonine (16).…”
Section: Alkaloids In Gelsemium Elegansmentioning
confidence: 99%
See 1 more Smart Citation
“…18.3 mg), 10-methoxycamptothecin (5, 4.3 mg), pumiloside (6,21.0 mg), (3R)-deoxypumiloside (7,26.3 mg) and strictosamide (8, 3.7 mg); b-carboline-type alkaloids, such as lyalosidic acid (9, 339.4 mg), ophiorine A (10, 5.6 mg), ophiorine B (11, 6.4 mg) and harman (12, 25.2 mg); and 13 known compounds (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The structures of the known compounds were deduced from spectroscopic data and confirmed by comparison with those of authentic samples or reported data.…”
mentioning
confidence: 99%